Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1021/jp066489l
|View full text |Cite
|
Sign up to set email alerts
|

From Controllable Attached Isolation Moieties to Possibly Highly Efficient Nonlinear Optical Main-Chain Polyurethanes Containing Indole-Based Chromophores

Abstract: For the first time, the indole-based NLO chromophores were embedded into the polymer main chain, and different isolation groups were attached to their donor side with the efforts of adjusting the NLO properties of the resultant main-chain polyurethanes, according to the site isolation principle. Thanks to the main-chain structure and the advantages of the indole-based chromophores, all the polymers show excellent transparency, good processability, thermal stability, and relatively good NLO effects. The tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 98 publications
3
26
0
Order By: Relevance
“…Furthermore, the exterior benzene moieties and the interior triazole rings played an important role in decreasing the interactions and enhancing the poling efficiency, according to the concept of "suitable isolation group". [14,15] As there might be some resonant enhancement due to the absorption of the chromophore moieties at 532 nm, the NLO properties of dendrimers should be smaller, as shown in Table 2 (d 33 (1)). Because of their wide optical transparency window (the maximum absorption wavelengths of their films were only around 470 nm), as well as their large d 33 values, the d 33 (1) values of …”
Section: G0-mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the exterior benzene moieties and the interior triazole rings played an important role in decreasing the interactions and enhancing the poling efficiency, according to the concept of "suitable isolation group". [14,15] As there might be some resonant enhancement due to the absorption of the chromophore moieties at 532 nm, the NLO properties of dendrimers should be smaller, as shown in Table 2 (d 33 (1)). Because of their wide optical transparency window (the maximum absorption wavelengths of their films were only around 470 nm), as well as their large d 33 values, the d 33 (1) values of …”
Section: G0-mentioning
confidence: 99%
“…[11] Fortunately, according to the experimental results and theoretical analysis of Jen, Dalton, and co-workers, the dendritic structure, present in dendrimers, hyperbranched polymers, and dendronized polymers (in which some isolation groups were bonded to the chromophore moieties to decrease the interactions and increase the poling efficiency by applying the site isolation principle), was considered a very promising molecular topology for the next generation of highly efficient NLO materials and expected to meet the basic requirements of practical applications: large macroscopic optical nonlinearity, high physical and chemical stability, and good optical transparency. [12,13] On the basis of their excellent work, and according to the concept of "suitable isolation group" summarized from the experimental results of our systematically research in the dendronized polymers, [14,15] we recently designed a new convergent approach to NLO dendrimers G1-G3 (Scheme S1 in the Supporting Information). [16] These dendrimers not only confirmed our thoughts on the formed triazole rings as the suitable isolation groups to enhance the macroscopic NLO effect, but, more excitingly, also demonstrated that accompanying the increased loading density of the chromophore moieties was an increase in the tested NLO effects.…”
mentioning
confidence: 99%
“…After bonding to the polymer chain, the maximum absorption wavelength of the chromophore moieties were blue‐shifted (upto 9 nm in the case of P4 ) compared with those of the free chromophore molecules. This occurred because of the electronic interaction between the chromophore moieties and the polymer chain 14…”
Section: Resultsmentioning
confidence: 99%
“…Jen and coworkers4, 8–10 prepared a series of NLO dendrimers and polymers containing dendronized moieties, which expressed ultrahigh macroscopic NLO activities due to the site isolation principle, which reduces intermolecular electrostatic interactions. Qin and coworkers11–14 synthesized various NLO polymers containing isolation groups in which the size of the isolation group was changed from small atoms such as hydrogen to much larger groups. They showed that a suitable isolation group boosts the microscopic molecular hyperpolarizability to a possibly higher macroscopic NLO property efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, there are the composites of low molecular compounds included in the neutral polymeric matrix [15,30] and their complexes [31]. Secondly, there are different types of polymers in which the diazo group is chemically incorporated into the polymer chain [27,32], or attached as side groups [25,26,29,33,34]. And thirdly, there are low molecular weight organic glasses (LMOG) capable of forming an optically uniform film of thickness up to several microns [11][12][13][14][43][44][45].…”
Section: Introductionmentioning
confidence: 99%